Advancements on scaling-up simulation of Proton Exchange Membrane Fuel Cells impedance through Buckingham Pi theorem. (1st September 2019) - Polverino, Pierpaolo; Bove, Giovanni; Sorrentino, Marco; Pianese, Cesare; Beretta, Davide
Highlights: Buckingham Pi theorem is applied to design fuel cells impedance scaling-up method. Generalized modelling is achieved through a phenomenological approach. Inference on physical parameters is achieved by means of inverse modelling. Physical reasoning on parameters distribution proved effective for scaling-up. Scaling-up technique validated on experimental data from single-cell to full stack. Abstract: This article addresses a generalized scaling-up technique applied to proton exchange membrane fuel cells. Such a methodology allows simulating the impedance related to a full stack from that of a single cell or short stack, combining experimental data with physical reasoning and phenomenological modelling. The use of such technique can reduce electrochemical impedance spectroscopy testing costs, with a significant impact on fuel cell manufacturing and performance assessment processes. The procedure described in this paper relies on a former approach, already presented by the authors, which has been improved with respect to two main aspects. Firstly, non-dimensional parameters are computed, by referring to the Buckingham Pi theorem, through a generalized physical model. Secondly, single cell or short stack internal states (i.e., water content and limiting current) are evaluated through significant information gained from impedance measurements and inverse modelling. Stack impedance simulation is performed through proper internal states distribution assumptions. To prove the consistency and robustness of the proposed technique, experimental data taken from the literature and the European funded project HEALTH-CODE are used, with stack impedance accurately reproduced by means of only a single cell spectrum.